Strategi Optimalisasi Retribusi Pelayanan Parkir Tepi Jalan Umum Berdasarkan Perda No. 1 Tahun 2024 - Laia, Juliana Adek Putri; Tobing, Artha Lumban; Pasaribu, Jonson (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study aims to analyze how the implementation strategy of on-street parking retribution can be optimized in accordance with the latest regulation outlined in Regional Regulation No. 1 of 2024. The research uses a descriptive qualitative method with a case study approach, where data was collected through interviews with parking managers, parking attendants, and analysis of related policy documents. The results show that although Regional Regulation No. 1 of 2024 has the potential to increase parking retribution, several obstacles were identified in its implementation, such as insufficient supervision, limited parking infrastructure, and irregularities in retribution collection. Therefore, it is recommended that local governments strengthen supervision mechanisms, improve parking facilities, and implement technology in the retribution collection system. This study is expected to contribute to regional policy in optimizing parking retribution to support regional development and improve public services.